Radiological findings of multisystem inflammatory syndrome in children associated with COVID-19 - Kalın, Sevinç; Sözeri, Betül (British journal of radiology, 2022)
To retrospectively evaluate the imaging and clinical findings of patients diagnosed with multisystem inflammatory syndrome in children (MIS-C) associated with COVID-19. The clinical, laboratory and radiological data of 110 patients (74 male and 36 female) diagnosed with COVID-19-related MIS-C between June 2020 and November 2021 were evaluated retrospectively. Cases with a diagnosis of MIS-C based on a positive real time polymerase chain reaction (RT-PCR) test or serology results according to the WHO criteria were included in the study. All the radiological data were evaluated by a pediatric radiologist with 14 years of radiology experience. Peribronchial thickening and hyperinflation were the most common findings on chest X-ray, while atelectasis and pleural effusion were often present in thoracic CT. Cardiac involvement was detected in 30% of the patients, mainly with valve insufficiency and systolic dysfunction, and 7.2% of these patients had sequalae findings. The most common abdominal findings were hepatosplenomegaly, mesenteric inflammation, lymphadenomegaly, thickening of the intestinal walls and free fluid. 23 of the patients had comorbidities. Neurological radiological findings observed in a total of six patients were reversible splenial lesion syndrome, posterior reversible encephalopathy syndrome, meningitis, and cerebral edema. 37 patients were followed up in the intensive care unit and 2 of them died. Radiological findings seen in MIS-C vary according to the affected system. There is no specific radiologic finding for this disease, but radiological findings can assist in the evaluation of affected systems and guide treatment. Since there are few studies with a limited number of patients in the literature, data on this subject are limited. We aimed to contribute to the literature with our large patient data.